Analisis maqashid dan maslahah transaksi e-commerce di Indonesia - Sri Wahyuni; Asmuni Asmuni; Tuti Anggraini (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to analyze the relevance and implications of Maqashid Syariah and Muamalah in e-commerce transactions in Indonesia. The aim of this study is to understand how the principles of Maqashid Sharia and Muamalah can be applied in the context of e-commerce transactions, as well as to identify the benefits and challenges that arise in applying those principles. This research method uses a qualitative approach by conducting a literature review involving the study of scientific literature, official documents, and practice guidelines related to e-commerce and Islamic economics. Qualitative analysis was conducted to explore and understand the implications of Maqashid Sharia and Muamalah principles in e-commerce transactions in Indonesia. The results showed that Maqashid Syariah and Muamalah have significant relevance in the context of e-commerce in Indonesia. The application of these principles can ensure halal in transactions, maintain fairness, protect consumers, and create a business environment with integrity. However, there are challenges in implementing these principles, including a lack of awareness and understanding of the principles of Islamic economics, differences in interpretation, and limitations in monitoring and enforcing the rules. Therefore, collaborative efforts are needed between the government, business actors, and related institutions to increase understanding, develop codes of practice, and increase supervision in e-commerce transactions in accordance with Maqashid Syariah and Muamalah.